Algebra and Its Applications : Proceedings of the International Conference held at Aligarh Muslim University, 2016 - Ashraf, Mohammad; Asma, Ali; Boua, Abdelkarim; Carini, Luisa; Chelvam, Thirugnanam Tamizh; Dar, Nadeem Ahmad; De Filippis, Vincenzo; Dhara, Basudeb; Gaikwad, Karuna Tulshiram; Idrissi, My Abdallah; Khan, Noor Mohammad; Lee, Tsiu-kwen; et al. (De Gruyter, 2018)
The series is aimed specifically at publishing peer reviewed reviews and contributions presented at workshops and conferences. Each volume is associated with a particular conference, symposium or workshop. These events cover various topics within pure and applied mathematics and provide up-to-date coverage of new developments, methods and applications.- Resumé vydavatel
Keywords: algebra; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences